Legal Protection of Women Workers in Garment Companies in Bandung Regency - Dewi, Sri Wulan Ratna (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Legal protection for working women is the fulfillment of basic rights that are inherent and protected by the State, meanwhile there are still many female workers who have to struggle to be able to exercise their rights to provide breast milk to their children. The existence of company support in terms of providing child care in the workplace, a special room for expressing breast milk, and sufficient rest time for expressing breast milk are several supporting factors for the success of exclusive breastfeeding. This research aims to find out how garment companies in Bandung give their female workers the right in the form of time to provide exclusive breastfeeding, as well as to find out the legal protection for female workers to provide exclusive breastfeeding based on Law no. 36 of 2009 concerning health is linked to Law no. 13 of 2003 concerning employment. Method: normative juridical is presented descriptively and analytically. Result: At the garment factory in Bandung district, there is no ideal place or room for breastfeeding or expressing breast milk, and special opportunities for breastfeeding or expressing breast milk have not been provided during working hours, which means the company has not implemented the provisions of the legislation. So it can be said that legal protection for female workers in garment factories in Bandung district is not optimal enough in protecting the right to breastfeed for female workers. Conclusion: In garment companies in Bandung Regency, there is no ideal place or room for breastfeeding or expressing breast milk, and special opportunities for breastfeeding or expressing breast milk have not been provided during working hours so the rights of female workers are not implemented and are not by the provisions regulated in Law no. 36 of 2009 concerning Health.